Kepastian Hukum Sertifikat Hak Cipta Sebagai Objek Jaminan Fidusia Dalam Praktik Perbankan: Analisis Normatif Dan Implementatif - Darojatun Andara (Diktum: Jurnal Ilmu Hukum, 2026)
The utilization of copyright certificates as objects of fiduciary security constitutes an alternative financing instrument with the potential to support the development of the creative economy and financial inclusion. Nevertheless, in Indonesian banking practice, the use of copyright as collateral continues to face various legal and regulatory challenges. This article aims to analyze the legal certainty of copyright certificates as objects of fiduciary security and to formulate an innovative and secure legal framework strengthening model applicable to banking practice. This study employs a normative legal research method using statutory, conceptual, and case approaches, through an analysis of the Copyright Law, the Fiduciary Security Law, banking regulations, as well as financing practices and relevant court decisions. The findings indicate that although copyright is normatively recognized as intangible movable property eligible for fiduciary security, substantive legal certainty has not been fully realized due to the absence of valuation standards, limitations in execution mechanisms, lack of integration within registration systems, and the absence of specific regulations governing intellectual property–based financing in banking law. This study proposes a legal certainty strengthening model encompassing cross-sector regulatory harmonization, registry interoperability, copyright valuation standardization, the formulation of execution guidelines, and enhanced collaboration between regulators and the banking sector. This model is expected to bridge the gap between normative recognition and practical implementation of intellectual property–based financing.